Analysis of the Total Physical Response (TPR) Method in Improving English Vocabulary Understanding of 5-6 Year Old Children - Mala, Elvita (CV. Creative Tugu Pena, 2025)
This study aims to analyze the effectiveness of the Total Physical Response (TPR) method in improving English vocabulary comprehension in children aged 5–6 years. Early age is an important period in language development, so a learning method is needed that is in accordance with the characteristics of children, one of which is the TPR method. This study was conducted through a literature study by reviewing various internationally reputable scientific journals that discuss the application of the TPR method in early childhood education (PAUD). The results of the study indicate that TPR is an effective method in improving vocabulary mastery through fun and participatory physical activities. Children are asked to respond to verbal instructions with body movements, such as pointing, running, or jumping according to the meaning of the words being learned. This approach makes it easier for children to associate vocabulary with real actions, thus strengthening their memory. The TPR method is very suitable for the cognitive and psychomotor development of early childhood children who tend to learn through concrete experiences. Through movement-based learning, children become more active, focused, and motivated. In addition, the learning atmosphere created is more interactive and free from pressure, because children are not forced to speak directly, but rather understand and respond to commands physically. The Total Physical Response method has been proven to be effective as an English teaching strategy for early childhood. This approach not only improves vocabulary, but also supports the development of motor skills, concentration, and children's self-confidence.